Paradigm shifts in recordkeeping responsibilities: Implications for ISO 15489's implementation - Joseph, Pauline; Debowski, S.; Goldschmidt, P. (Emerald Group Publishing Limited, 2012)
Purpose: The purpose of this paper is to point out paradigm shifts in recordkeeping responsibilities from records and information management professionals (RIM professionals) to knowledge workers, caused by advancements in information and communication technologies and by user and organizational expectations. The impact of these changes on the implementation of professional records management (RM) principles and guidelines particularly in ISO 15489 is discussed. Design/methodology/approach: The paper looks at the issues from an academic viewpoint by reviewing ISO 15489's RM principles presented in Part 1 and guidelines in Part 2 of the standard. The currency of the standard in capturing the changing practices that are flowing into RM approaches are then evaluated against four of the principles. These four principles are reviewed against three key paradigm shifts.Findings: The authors present evidence of significant paradigm shifts relating to changing technology, work practices, devolution of recordkeeping responsibilities to users, their growing expectations, and increasing organizational concerns for RM accountability. These are generating pressure on RM systems to change and become more responsive. This review highlights the critical need to better appreciate the changing RM context and its implications for broader policy and professional practice.Practical implications: The key practical implication identified in the paper relates to reconceptualisation of the roles of RIM professionals, knowledge workers and senior management for recordkeeping. Social implications: The changing nature of RM in organizations will necessitate stronger engagement of knowledge workers and senior management with their RM services. Originality/value: This paper focuses on the user responsibilities for RM versus traditional RIM professionals having this role. The paper offers an innovative view of professional RM practice and suggests some new directions for RIM professionals to better accommodate user needs and expectations.